the Relation of common ABL kinase domain mutations with resistance to Tyrosine Kinase Inhibiters in patients with Chronic Myeloid Leukemia in Middle Euphrates of Iraq: Chronic Myeloid Leukemia in Middle Euphrates of Iraq - Mahdi Al- Musawi, Mohammed Sadeq; Raheem, Raheem Mahdy; Mahdi, Liwaa Hussein; Al-Yasiri , Israa Ketab (International Journal of Scientific Research and Management (IJSRM), 2020)
Background : Chronic myeloid leukemia (CML) is a hematopoietic stem cell disease, associated with a reciprocal translocation between chromosomes 9 and chromosome 22, lead to the formation of the BCR-ABL fusion gene (Philadelphia chromosome). This fusion gene is believed to play golden role in the initial development of CML with constitutive tyrosine kinase activation.   Successful use of tyrosine kinase inhibiters (TKIs) play a role in improve survival and increase prevalence of CML, but un fortunately   mutations in the BCR-ABL kinase domain may cause, or contribute to increase, resistance to TKIs in CML patients.  .Objective: This study was designed to assess the association of five most common BCR-ABL kinase domain mutations (T315I, M351T, E255K, M244V and E255V) with resistance state of CML patients on TKIs in Iraqi Middle Euphrates region.Patients and methods: A retrospective case-control study in which  85  patients with chronic myeloid leukemia in chronic phase (45 patients as cases group and 40 patient as control group) were selected from three hemato-oncology centers in middle Euphrates in Iraq during the period from January 2016 till October  2016 out of a total of  240  CML patients ( 108 male and 132 female) who were registered during this period in these three centers  and all patients on TKI (Imatinib and Nilotinib). Venous blood sampling done for BCR-ABL kinase domain mutations screening.Results:  four patients from cases group (4/45) were carriers of one of five selected ABL kinase domain mutations and no one of control group. T315I mutation was detected in 3/45 (6.6 %) of resistant patients, with a significant risk association to develop resistance to TKI therapy (odd ratio and C. I. ) (6.67, 0.3340 -133.2255). E255V was detected in 1/45 ( 2.2 %) and also had  significant risk association to develop resistance to TKIs( odd ratio, C.I.) (2.73, 0.1081 -68.9424). No one of these mutation had significance correlation with demographic or hematological features. M351T, E255K and  M244V were not detected in any one of our study groups CML patients.Conclusions: T315I and E255V among five ABL kinas domain mutations were detected in our CML patients with resistance to TKIs. All of them may play a role in development variable degree of resistance to first and second generation TKIs weather primary or secondary.T315I mutation is most common mutation within  BCR-ABL domain kinase gene.